2008
DOI: 10.1007/s10551-008-9754-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Implicit Moral Attitudes on Managerial Decision-Making: An Implicit Social Cognition Approach

Abstract: business ethics, ethical decision-making, implicit association test (IAT), implicit attitudes, implicit social cognition, mental processes, moral judgements,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 73 publications
0
30
0
Order By: Relevance
“…Applying such claims to the ethical decision-making process, it seems reasonable to argue that the rationalist approach would consider moral reasoning as one of the processes of System 2, being the cognitive process system that any individual activates to evaluate carefully a situation, come up with a conscious and deliberate decision, and structure a course of action (Marquardt and Hoeger 2009;Provis 2015;Woiceshyn 2011). In contrast, intuitive judgment or moral intuition, being unconditional and spontaneously triggered, seems to be associated with the automatic reply of System 1 (see Fig.…”
Section: The Rationalist Tradition Of Ethical Decision Makingmentioning
confidence: 99%
See 3 more Smart Citations
“…Applying such claims to the ethical decision-making process, it seems reasonable to argue that the rationalist approach would consider moral reasoning as one of the processes of System 2, being the cognitive process system that any individual activates to evaluate carefully a situation, come up with a conscious and deliberate decision, and structure a course of action (Marquardt and Hoeger 2009;Provis 2015;Woiceshyn 2011). In contrast, intuitive judgment or moral intuition, being unconditional and spontaneously triggered, seems to be associated with the automatic reply of System 1 (see Fig.…”
Section: The Rationalist Tradition Of Ethical Decision Makingmentioning
confidence: 99%
“…In particular, the emotional processing is a significant mediator function played by affects and emotions channeling decision makers' intuiting toward affectively charged intuitions (Greene et al 2001;Haidt 2001). This emotional processing encapsulates the experiential state of the decision maker during the actual circumstances, therefore playing a significant role in determining intuitive moral judgments (Greene et al 2001;Marquardt and Hoeger 2009;Whitaker and Godwin 2013). For the purpose of a blended model of ethical decision making, it is important to acknowledge the existence of different types of emotions impacting on the ethical decision-making process, as will be presented clearly in the framework later, specifying that emotions affecting the intuitive and instinctual decision-making process, or moral intuition, belong to the 'hot' system.…”
Section: The Role Of Emotion In Moral Intuitionmentioning
confidence: 99%
See 2 more Smart Citations
“…reasoning is a post-hoc attribution (Monin, Pizzaro, & Beer, 2007) thereby creating an illusion of control (Dane & Pratt, 2009;Sonenschein, 2007). In an experimental study using a deliberative ethical decision-making task Marquardt and Hoeger (2009) found that managers' implicit (intuitive) moral attitudes exercised an important influence on their decision-making; they concluded that complex and deliberative decision-making processes in the context of business ethics are significantly affected by implicit moral attitudes. Even though individuals may ascribe their moral judgments and behaviors to rationality, intuitionist theories suggest that "individuals first use intuitions and then use post-hoc (moral) reasoning" (Sonenschein, 2007(Sonenschein, , p.1027.…”
Section: Moral Intuitionmentioning
confidence: 99%